Multivariate statistical analysis - Giri, Narayan C., 1928- (Statistics, textbooks and monographs, 2004)
The second edition of this text adds topics in properties and characterization of symmetric distribution, elliptically symmetric multivariate distributions, singular symmetric distributions, estimation of covariance matrices, tests of mean against one-sided alternatives and more.